Public Signs in Objek Wisata Candidasa (OWC): Linguistic Landscape Study - I Made Astu Mahayana; Made Sani Damayanthi Muliawa; I Gusti Ayu Agung Dian Susanthi (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
Research on Linguistic Landscape (LL) has been done quite often in recent years. The studies are still focused on examining signs in one particular area. In this regard, this study aimed to examine the public signs found in the tourism area of Objek Wisata Candidasa (Candidasa Tourism Objects), Bugbug Village, Karangasem. This place was chosen since Objek Wisata Candidasa (OWC) is one of the tourism destinations in Bali most at risk of globalization. The current globalization affects the use of language on public signs around OWC. Furthermore, this study examines the language variation on public signs and the formers' motives in producing such language(s). The data in this research were the photograph of visible public signs in OWC supported by written and spoken information. For this research to be successful, this study applied the LL